Portion size has sustained effects over 5 days in preschool children: a randomized trial - Smethers, Alissa D (Am J Clin Nutr, 2019)
BACKGROUND: Although short-term studies have found that serving larger portions of food increases intake in preschool children, it is unknown whether this portion size effect persists over a longer period or whether energy intake is moderated through self-regulation. OBJECTIVES: We tested whether the portion size effect is sustained in preschool children across 5 consecutive days, a period thought to be sufficient for regulatory systems to respond to the overconsumption of energy. METHODS: With the use of a crossover design, over 2 periods we served the same 5 daily menus to 46 children aged 3–5 y in their childcare centers. In 1 period, all foods and milk were served in baseline portions, and in the other period, all portions were increased by 50%. The served items were weighed to determine intake. RESULTS: Increasing the portion size of all foods and milk by 50% increased daily consumption: weighed intake increased by a mean ± SEM of 143 ± 21 g/d (16%) and energy intake increased by 167 ± 22 kcal/d (18%; both P < 0.0001). The trajectories of intake by weight and energy across the 5-day period were linear and the slopes did not differ between portion conditions (both P > 0.13), indicating that there were sustained increases in intake from larger portions without compensatory changes over time. Children differed in their response to increased portions: those with higher weight status, lower ratings for satiety responsiveness, or higher ratings for food responsiveness had greater increases in intake from larger portions (all P < 0.03). CONCLUSIONS: This demonstration that preschool children failed to adjust their intake during prolonged exposure to larger portions challenges the suggestion that their self-regulatory behavior is sufficient to counter perturbations in energy intake. Furthermore, overconsumption from large portions may play a role in the development of overweight and obesity, as the magnitude of the effect was greater in children of higher weight status. This trial was registered at www.clinicaltrials.gov as NCT02963987.